(untitled) (Current Problems in Rail Vehicles, 2025)
The paper describes current projects of dual locomotives in CZ LOKO, a.s. In the first part it describes the process of development, production, setting up, functional and type tests and initial experience with operation of DS2000 DC locomotives (190.0 / 744.5 series), which is a variant of the dual locomotive enabling the use of energy from the 3 kV DC overhead line or from the CAT C32 internal combustion engine. The following is a description of the currently designed dual locomotive for the 25 kV 50 Hz and 15 kV 16.7 Hz voltage systems in combination with the more powerful CAT C32 B internal combustion engine. This locomotive is the basis of a completely new platform that should serve as the basis for the development of future locomotive series. Emphasis is placed on the development of the main frame and cab, which have to be redesigned, particularly because of the difficulty of accommodating all the necessary components while maintaining the weight and dimensions of the locomotive.